(untitled) - Brown, Lawrence A. (London, 1981)
This book diffusion research in geography thematic account. The market and infrastructure perspective. The market and infrastructure perspective. A note on the diffusion of innovation among firms.
Keywords: Đổi mới công nghệ,Technological innovations